THE EFFECT OF PROBLEM BASED LEARNING WITH TEAM ASSISTED INDIVIDUALIZATION, PROBLEM BASED LEARNING WITH THINK PAIR SHARE, AND COGNITIVE MODELS ON LEARNING OUTCOMES - Wasilah, Umi; Rufi’i, Rufi’i; Suhari, Suhari (PEDAGOGIK : JURNAL PENDIDIKAN, 2023)
This study was to determine the effect of a combination of problem-based learning with team-assisted individualization, problem-based learning with think pair share, and cognitive style on learning outcomes. This type of research is a quasi-experimental design that uses a 2x2 factorial design. The research population was XI Mathematics and Natural Science (MIPA) students in SMAN 1 Kraksaan and XI Mathematics and Natural Science (MIPA) of SMAN 1 Paiton Probolinggo, East Java, Indonesia, in 2022/2023. the samples were selected non-randomly, consisting of problem-based learning with team-assisted individualization (control) and PBL-TPS (experimental) groups. In both groups, given cognitive style test. The research instrument was 25 multiple-choice questions. Instrument validation is valid (0.89) and reliable (0.94). Posttest results were analyzed by two-way ANOVA test through SPSS v. 25. The study's results were; 1) There are differences in learning outcomes between problem-based learning with team-assisted individualization groups and problem-based learning with think pair share; 2) There are differences in learning outcomes between groups of cognitive style Field Dependent with cognitive style Field Independent; and 3) There is no interaction between learning models and cognitive styles on learning outcomes.